TUC Progress of Strike Report No. 7, 11 May 1926 (4pm) (page 1)
1926-05-11 "TUC Progress of Strike Report No. 7, 11 May 1926 (4pm) (page 1)" [g0033001.jpg], 11 May 1926, Trades Union Congress The Nine Days